ANALISIS DATA SURVEI PRESSURE-TEMPERATURE-SPINNER (PTS) PADA SUMUR PANASBUMI DUA FASA - Ardhana H, Shanni
Pressure-Temperature-Spinner (PTS) logging survey is conducted in two-phases geothermal well, well S. The result data in this survey are pressure, temperature, and spinner revolution frequency data. By using spinner revolution frequency data and cable speed, fluid velocity on well depth can be calculated. Mass ratecan be calculated after fluid velocity data are known. In two-phase fluid flow, there is dryness factor needed in entalphy calculation. By knowing fluid velocity, mass rateand entalphy from result data, along with depth pressure and temperature, feedpoint position and contribution can be predicted. A wellbore simulation program is needed to confirm feedpoint position and contribution predicted by matching the observation data. The matching process is prioritized based on tools accuration to ease noised observation data matching process. As the result of method application to well S, two-phase fluid flow model is developed and five feedpoints is predicted.